To the question of the newest trends in political processes in Latin America: prospects and challenges - Liudmila Okuneva (Ибероамериканские тетради)
The article deals with the major political problems of Latin America recently: the right drift, the conflict potential of political systems leading to the so called “divided power” (conflict between the Executive and Legislative branches of government), the function of the judicial power etc.